Contemporary Challenges and Opportunities for Improved Lawn Weed Management: Insights from U.S. Lawn Care Operators. (1st June 2022) - Ervin, David; Dixon, Lori Mitchell; Montry, Andrew; Patton, Aaron; Bowling, Becky; Elmore, Matthew; Gannon, Travis; Kaminski, John; Kowalewski, Alec; McCurdy, Jay; McElroy, J. Scott; Unruh, J. Bryan; et al.
Lawns provide valuable ecological, economic and social services. Both the quantity and quality of the turfgrass affect the level of the services delivered. Unwanted weed infestations can degrade lawn quality and decrease the value of these services for lawn users and others. For example, Brosnan et al. reported that athletic fields with weed cover not only decreased aesthetic quality but also resulted in increased surface hardness and a concomitant increase in potential athlete injuries and soil erosion. Contemporary research pertaining to pest influences on lawn quality and management responses is sparse. We hope to begin filling that gap with findings from a recent study of U.S. lawn care operators about the challenges and opportunities omanaging Poa annua, an emergent threat to sustainable lawn management (USDA-NIFA Specialty Crops Research Initiative (SCRI) Grants Program (award #: 2018-51181-28436). Estimates for residential- and commercial-lawn cover in the United States (U.S.) range from 58, 000 km2 to 120, 000 km2 with total turfgrass cover (inclusive of golf courses, parks, schools, roadsides) estimated at 163, 800 km2. The Federal Highway Administration (FHWA) estimated that there are 20, 436 km2 of grassed rights of way (roadsides) in the U.S. The total U.S. urban area in 2010 was estimated at 802, 053 km2. Together, we can estimate turf cover between 7 and 18% of U.S urban areas, including lawns as the primary turf surface along with parks, athletic fields, golf courses, and roadsides. The professional lawn care industry employed 295, 000 workers and represented an 18.5 billion market value in 2002. Despite its size, the U.S. lawn care industry defies simple characterization in part due to its heterogeneity. Lawns may provide valuable ecosystem services, including wildlife habitat, water infiltration, and moderation of the urban heat-island effect as well as aesthetics and open space for recreation. Apart from offering economic and ecological services, lawns and their management can be an important component of community social character and culture. Effective weed management in lawns assures sustainable delivery of all of these services, such that lawns are uniform and free from potentially troublesome weed species, such as Poa annua which ranks as the #1 most troublesome weed in turfgrass systems.